(untitled) (Revista Científica Tecnológica - ISSN: 2708-7093, 2018)
The sanitary quality of the surface and subterranean waters of the Rio Viejo Sub-basin was studied during the dry season (March 2010) and the rainy season (January 2011). The study was based on the analysis of thermotolerant Coliform organisms, Escherichia coli, Fecal Streptococci and Enterococci. Of the sixteen sampling sites examined, on the Río Viejo and its tributaries, only two, Apanás lake and Abra Vieja were found suitable for recreational use. The thermotolerant Coliforms and Escherichia coli were consistently detected in both study seasons. Of the seven springs studied, only Pacaya, for the dry season and El Pavón, for the rainy season, were found suitable for consumption. As for the wells drilled (10 in total), Santa Rosa and Tatascame, for dry season and Namanji, Los Arados and Santa Bárbara, for the rainy season, can be used for consumption purposes. The others, exceeded the criteria of W.H.O, 2011, so that they can be used for consumption purposes. The bacterial concentrations, detected in the excavated wells (3 in total) indicate that they are exposed to contamination by organic residues of human and animal origin, resulting to be unfit for consumption. The results obtained show that surface and groundwater are being influenced by activities of anthropogenic origin and that there is a contamination of fecal origin, which represents a potential risk to the health of the population.